2012
DOI: 10.1074/jbc.m112.347120
|View full text |Cite
|
Sign up to set email alerts
|

ADAM15 Protein Amplifies Focal Adhesion Kinase Phosphorylation under Genotoxic Stress Conditions

Abstract: Background: ADAM15 confers apoptosis resistance to chondrocytes upon exposure to genotoxic stress. Results: Apoptosis induction provokes direct ADAM15 binding to focal adhesion kinase (FAK) and an associated enhanced phosphorylation of the FAK-Src complex. Conclusion: ADAM15 interacts with FAK-Src, thereby enhancing survival signals. Significance: The anti-apoptotic ADAM15 signaling has potential relevance to tumorigenesis beyond its impact on chondrocyte survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 41 publications
0
36
0
1
Order By: Relevance
“…We previously showed that OA chondrocytes respond to genotoxic stress conferred by camptothecin with an increase in phosphorylation of FAK and Src. In the presence of ADAM15, FAK and Src signaling is considerably amplified (). To study whether RASFs also activate Src and FAK in response to either genotoxic stress or receptor‐triggered apoptosis, the cells were incubated for 0–60 minutes with camptothecin or FasL, and cell lysates were subjected to immunoblotting using antibodies specific for FAK Y 576 , Y 861 , or the autophosphorylation site Y 397 , as well as antibodies specific for Y 416 of Src.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously showed that OA chondrocytes respond to genotoxic stress conferred by camptothecin with an increase in phosphorylation of FAK and Src. In the presence of ADAM15, FAK and Src signaling is considerably amplified (). To study whether RASFs also activate Src and FAK in response to either genotoxic stress or receptor‐triggered apoptosis, the cells were incubated for 0–60 minutes with camptothecin or FasL, and cell lysates were subjected to immunoblotting using antibodies specific for FAK Y 576 , Y 861 , or the autophosphorylation site Y 397 , as well as antibodies specific for Y 416 of Src.…”
Section: Resultsmentioning
confidence: 99%
“…Synovial fibroblasts (1 × 10 4 or 1 × 10 5 ) were seeded in 96‐ or 24‐well culture plates and grown for 24 hours. Cells were treated with 20 n M Silencer Select predesigned small interfering RNAs (siRNAs; Ambion) for ADAM15 as described previously (). Nonsilencing siRNA Control #1 (Ambion) was used as the negative control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ADAM15 and acrogranin have been related to cell adhesion exerting apoptosis resistance and survival effects on different cell lines (He et al 2002, Guerra et al 2007, Ryan et al 2009, Bö hm et al 2010, Cuevas-Antonio et al 2010, Rosen et al 2011, Hou et al 2013. These effects could be related to the modulation of focal adhesion kinase signaling through activation of Src (Fried et al 2012, Bö hm et al 2013 as well as the formation of a complex involving paxillin, FAK, and ERK (He et al 2002, Monami et al 2006, Ryan et al 2009). Remarkably, a recent report has suggested the presence of phosphorylated FAK in horse spermatozoa (Gonzalez-Fernandez et al 2013) and findings in our laboratory has indicated an increase in the phosphorylation of FAK and paxillin during sperm capacitation (data not shown).…”
Section: P<0002mentioning
confidence: 99%